Popularity and knowledge concerning complications of body modifications among young adults - Pekar, Joanna; Skolarczyk, Justyna; Łabądź, Dawid; Chrobok, Katarzyna; Nieradko-Iwanicka, Barbara (Polish Journal of Public Health, 2018)
Introduction. Body modifications are practices leading to transient or permanent change of various parts of human body. The most popular forms of body modifications are tattooing and piercing.Aim. The aim of the study is to determine the frequency of the most popular body modifications (tattoos and piercing) among young adults aged 18-32 years and to collect and analyze their opinions concerning body modifications and to determine their knowledge about the complications during these procedures.Material and methods. The study was conducted in February 2017 among 251 individuals: 146 females (58.17%) and 105 males (41.83%). An original questionnaire was used. It consisted of questions about body modifications. Researchers recorded body modifications the respondents have had. Participation in the study was voluntary and anonymous. Participants were randomly selected. Results were analyzed with STATISTICA 12.5 and ANOVA program; p